Dentists' utilization of caries risk assessment and individualized caries prevention methods in pediatric patients in Saudi Arabia - Ammar T Asali; Fawaz Pullishery; Vani Taneja; Hadil I A. Wajih; Duna J Z. Basrawi; Alaa A S. Alrashid; Dana A A. Alogaly; Ruqayya I A. Gaya; Mohamed S A. Elnawawy (Wolters Kluwer Medknow Publications, 2023)
Introduction: The first step in any complete oral health care plan for a child is a thorough caries risk assessment (CRA). This study aimed to investigate whether the practice dentists in Saudi Arabia's Western province do CRA methods and offer Individualized Caries Prevention (ICP) to their pediatric patients. Material and Methods: Dentists in active clinical practice in the Western province of Saudi Arabia were the participants of this cross-sectional survey. The participants in this study were chosen using a simple random sampling technique. A self-administered, structured questionnaire was used to gather participants' responses. Results: A majority (88.2%) of the dentists agreed that it is very important to practice CRA on a regular basis among their pediatric patients. About 67% of dentists employed Individualized Caries Prevention methods. No statistically significant correlation was observed between ICP and CRA factors, indicating that interventions primarily focused on patients' financial affordability. Conclusion: Dentists should encourage parents/caregivers to establish a dental home concept at the earliest, which includes CRA, education, and anticipatory guidance on the prevention of oral diseases.